Botanical Gardens, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2009)
A part of the Botanical Gardens is shown in this picture, among the scattered trees are a variety of tropical plants. Affixed to the back of the postcard are two Trinidad and Tobago stamps, a 6 cents and a 3 cents.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Trees--Trinidad and Tobago; Plants--Trinidad and Tobago; 1940